2015
DOI: 10.3389/fimmu.2015.00166
|View full text |Cite
|
Sign up to set email alerts
|

Drugs to Block Cytokine Signaling for the Prevention and Treatment of Inflammation-Induced Preterm Birth

Abstract: Preterm birth (PTB) at less than 37 weeks of gestation is the leading cause of neonatal morbidity and mortality. Intrauterine infection (IUI) due to microbial invasion of the amniotic cavity is the leading cause of early PTB (<32 weeks). Commensal genital tract Ureaplasma and Mycoplasma species, as well as Gram-positive and Gram-negative bacteria, have been associated with IUI-induced PTB. Bacterial activation of Toll-like receptors and other pattern recognition receptors initiates a cascade of inflammatory si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 90 publications
1
54
0
2
Order By: Relevance
“…Together, these results indicate that (+)-naloxone is a useful experimental drug for investigating the utility of small molecule TLR inhibitors as pharmacological agents that might be administered in association with antibiotics to contain infection and suppress progression to preterm birth53. While clearly there are major challenges to consider in extrapolating this work to clinical application, we speculate that such TLR4 inhibitors may have particular value as prophylactic agents in threatened preterm labour where increased TLR4 expression disposes to elevated susceptibility, even in the absence of infection6061, or when TLR4 SNPs associated with an increased risk of PTD and premature rupture of membranes are identified6263.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Together, these results indicate that (+)-naloxone is a useful experimental drug for investigating the utility of small molecule TLR inhibitors as pharmacological agents that might be administered in association with antibiotics to contain infection and suppress progression to preterm birth53. While clearly there are major challenges to consider in extrapolating this work to clinical application, we speculate that such TLR4 inhibitors may have particular value as prophylactic agents in threatened preterm labour where increased TLR4 expression disposes to elevated susceptibility, even in the absence of infection6061, or when TLR4 SNPs associated with an increased risk of PTD and premature rupture of membranes are identified6263.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies identify downstream agents of TLR4-driven inflammation as additional effective targets for inhibiting infection-induced preterm birth53. Experiments in null mutant mice implicate IL1 and IL6, cytokines induced by TLR4 activation of NFκB, in amplifying and accelerating the birth cascade4147, while anti-inflammatory IL10 suppresses IL1 and IL6 production and protects against LPS-induced preterm birth4854.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs are primarily inhibitors of inflammatory pathway. Their targets included inhibition of NF-κB [5558], enhancers of antiinflammatory peroxisome proliferator activated receptor (PPARs) [59], and antioxidant N-acetyl cysteine[60,61], cytokine suppressive anti-inflammatory drugs [62,63], agents to regulate Glycogen synthase kinase 3 (GSK3), an enzyme crucial for inflammation homeostasis [64], surfactant protein-A and PGJ2 to down regulate TLR mediated inflammation [65,66], targeted IL-6[67], and IL-1β signaling [68] to reduce inflammation, over antiinflammatory suppression using IL-10[6971]. Although many of these (drugs) agents were successful in reducing inflammation or oxidative stress in vitro, some of them were shown to have toxic side effects in animal model trials or in clinical trials, and successful clinical trial outcomes are thus yet to be reported using any of these agents in reducing the risk of PTB.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of danger signals responsible for such inflammatory processes has not been determined [156, 177186]. However, it is possible that patients with sterile intra-amniotic inflammation may benefit from anti-inflammatory agents rather than antibiotics [187192]. Sterile intra-amniotic inflammation could be detected when a patient has a positive amniotic fluid MMP-8 rapid test but is negative for bacteria and virus when a combination of cultivation and molecular microbiologic techniques is used.…”
Section: Discussionmentioning
confidence: 99%